PERFORMANSI DUSUNG PALA SEBAGAI SALAH SATU AGROFORESTRI TRADISIONAL DI MALUKU - L Salampessy, Messalina; Bone, Iskar; Febryano, Indra Gumay (jurnal TENGKAWANG, 2012)
Management of dusung nutmeg is one form of land use systems and community-based forests can provide economic benefits, ecological and socio-cultural. This study aims to describe and explain management performance (productivity, sustainability, equity and efficiency benefits) of dusung nutmeg as a traditional agroforestry system in Maluku. The results showed: dusung formation in the Moluccas through three phases, namely gardens/fields phase, aong (former mixed farms left) phase and dusung phase. Dusung have aspects in terms of economic development, environment and management is essential for the development of its performance. The results show that (1) the cost structure and revenue productivity of farmers nutmeg correlated with the number of plants grown, (2) efforts cultivating and securing is done by the owner with the help of kewang (rangers) are assigned to secure dusung and implementation of sasi, this shows the orientation of the productivity and sustainability, (3) public priorities in dusung management is commercial needs for nutmeg and cloves and subsistence for vegetables, (4) raising dusung relatively efficient if calculated by the ratio of input and output production, and institutional is looked clearly the rights associated with ownership, control, management and so on as well as the availability of and respect for the rules to be mutually agreed between dusung owners, managers, harvesters and the surrounding communities. Keywords: agroforestry, dusung pala, performanc